1996
DOI: 10.3164/jcbn.20.83
|View full text |Cite
|
Sign up to set email alerts
|

Dietary N-3 Fatty Acid Supplementation in Rheumatoid Arthritis-Mechanisms, Clinical Outcomes, Controversies, and Future Directions.

Abstract: 83 84 D. VQLKER and M. GARG of confusion is that the level of supplementation with n-3 fatty acids has not been dose related, and there has not been any control of linoleic acid levels in the background diet. The purpose of this article is to review the recent studies utilizing n-3 fatty acids in clinical investigations of patients with rheumatoid arthritis and to suggest directions for future research efforts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 45 publications
1
13
0
Order By: Relevance
“…Further studies are needed to investigate how n-3 PUFA control mRNA levels and activities of aggrecanases and inflammatory mediators in the bovine and human in vitro models of arthritis, and whether a common mechanism exists for the alteration of gene transcription by n-3 PUFA. These findings add further weight to the epidemiological and clinical studies that have reported the benefits of dietary supplementation of n-3 PUFA in reducing pain and inflammation in human arthritic diseases (Volker & Garg, 1996;Cleland & James, 2000;Calder, 2001;Calder & Zurier, 2001), and suggest molecular mechanisms as to how these benefits occur.…”
Section: Discussionmentioning
confidence: 53%
“…Further studies are needed to investigate how n-3 PUFA control mRNA levels and activities of aggrecanases and inflammatory mediators in the bovine and human in vitro models of arthritis, and whether a common mechanism exists for the alteration of gene transcription by n-3 PUFA. These findings add further weight to the epidemiological and clinical studies that have reported the benefits of dietary supplementation of n-3 PUFA in reducing pain and inflammation in human arthritic diseases (Volker & Garg, 1996;Cleland & James, 2000;Calder, 2001;Calder & Zurier, 2001), and suggest molecular mechanisms as to how these benefits occur.…”
Section: Discussionmentioning
confidence: 53%
“…Each of these trials indicates benefits of fish oil which include reduced duration of morning stiffness, reduced number of tender or swollen joints, reduced joint pain, reduced time to fatigue, increased grip strength and decreased use of non-steroidal anti-inflammatory drugs. Details of these trials are reviewed elsewhere (Volker & Garg, 1996;James & Cleland, 1997;Geusens, 1998;Calder, 2001a,b;Calder & Zurier, 2001). In an editorial commentary discussing the use of fish oil in rheumatoid arthritis Cleland & James (2000) conclude that 'the findings of benefit from fish oil in rheumatoid arthritis are robust', that 'dietary fish oil supplements in rheumatoid arthritis have treatment efficacy', and that 'dietary fish oil supplements should now be regarded as part of the standard therapy for rheumatoid arthritis'.…”
Section: Rheumatoid Arthritis: a T-helper 1-type Disordermentioning
confidence: 99%
“…Such benefits include reduced duration of morning stiffness, reduced number of tender or swollen joints, reduced joint pain, reduced time to fatigue, increased grip strength and decreased use of non-steroidal anti-inflammatory drugs (Table 1). A number of reviews of these trials have been published (84)(85)(86)(87)(88)(89)(90) and each has concluded that there is benefit from fish oil. In an editorial commentary discussing the use of fish oil in RA it was concluded that 'the findings of benefit from fish oil in rheumatoid arthritis are robust', 'dietary fish oil supplements in rheumatoid arthritis have treatment efficacy' and 'dietary fish oil supplements should now be regarded as part of the standard therapy for rheumatoid arthritis' (91) .…”
Section: Trials Of N-3 Pufa In Rheumatoid Arthritismentioning
confidence: 99%